PREPARATION OF SERBIAN AGRICULTURAL INDUSTRY FOR EUROPEAN INTEGRATION - Vlahović, Branislav; Tomić, Danilo; Gulan, Branislav (Economics of Agriculture, 2006)
The authors of this work are analyzing agricultural resources of European Union, then taking a look back at the state of domestic agricultural industry, with a specific attention being given to it`s preparation for European integrations. They are showing the perspectives, chalenges and consequences of our country entering the European Union. They are emphasizing the lack of preparation of our agricultural industry for the chalenges it will have to face with, in this European integration.